2023
DOI: 10.5194/se-14-137-2023
|View full text |Cite
|
Sign up to set email alerts
|

Seismic amplitude response to internal heterogeneity of mass-transport deposits

Abstract: Abstract. Compared to unfailed sediments, mass-transport deposits are often characterised by a low-amplitude response in single-channel seismic reflection images. This “acoustic transparency” amplitude signature is widely used to delineate mass-transport deposits and is conventionally interpreted as a lack of coherent internal reflectivity due to a loss of preserved internal structure caused by mass-transport processes. In this study we examine the variation in the single-channel seismic response with changing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
0
0
Order By: Relevance
“…The visually deformed and disrupted nature of the sediment comprising Deposit 2a at this site is consistent with the mostly acoustically transparent nature of the deposit in Parasound profiles. Although even small amounts of deformation may have large consequences for the seismic character of a sedimentary unit (Ford et al, 2023;Karstens et al, 2023), the seismic character suggests that the deformation observed in the cores is laterally extensive and may imply disaggregation and loss of structures within the materials mobilized in this part of Deposit 2a (Figure 6). NW/SE oriented seismic profiles show that emplacement of the blocky center and of the smooth-surfaced apron occurred broadly on the same bottom surface, although seismic amplitudes are much higher and more continuous in the apron (Figures 2b and 2c).…”
Section: Sediment Erosion Incorporation and Deformationmentioning
confidence: 99%
“…The visually deformed and disrupted nature of the sediment comprising Deposit 2a at this site is consistent with the mostly acoustically transparent nature of the deposit in Parasound profiles. Although even small amounts of deformation may have large consequences for the seismic character of a sedimentary unit (Ford et al, 2023;Karstens et al, 2023), the seismic character suggests that the deformation observed in the cores is laterally extensive and may imply disaggregation and loss of structures within the materials mobilized in this part of Deposit 2a (Figure 6). NW/SE oriented seismic profiles show that emplacement of the blocky center and of the smooth-surfaced apron occurred broadly on the same bottom surface, although seismic amplitudes are much higher and more continuous in the apron (Figures 2b and 2c).…”
Section: Sediment Erosion Incorporation and Deformationmentioning
confidence: 99%